Fostering Religious Moderation through Literary Exploration: A Case Study of S.K. Ali’s Love from A to Z in University Classrooms - Dahlan Dahlan; Nurdin Nurdin; Mariano Satya Pramularsih; Akram Ista (STAI Hubbulwathan Duri, 2025)
In multicultural societies, promoting religious moderation in higher education is essential for fostering tolerance and interfaith understanding. Literature, particularly contemporary Muslim narratives, offers a unique medium for exploring these values. This study investigates the use of Love from A to Z by S.K. Ali as a pedagogical tool to cultivate religious moderation among university students. The research aims to assess how literary engagement with Muslim identities and interfaith dynamics influences students’ critical awareness and empathetic understanding of religious and cultural diversity. Employing a qualitative case study approach, the study involved 30 undergraduate students enrolled in a literature and religion course at an Indonesian university. Data were collected through classroom observations, reflective journals, and semi-structured interviews. Thematic analysis was used to identify key patterns in students’ responses to the text. The findings indicate that reading and discussing Love from A to Z enhanced students’ interfaith empathy, critical engagement with religious representation, and appreciation of pluralism. The novel’s portrayal of everyday Muslim experiences prompted students to reflect on personal biases and societal assumptions, leading to more nuanced perspectives on religious identity and coexistence. Integrating diverse literary narratives into the university curriculum can effectively foster religious moderation by promoting empathy, dialogue, and critical thinking. This study highlights the pedagogical value of literature in nurturing inclusive worldviews in higher education contexts.